2022
DOI: 10.3390/biom12111599
|View full text |Cite
|
Sign up to set email alerts
|

Thioterpenoids as Potential Antithrombotic Drugs: Molecular Docking, Antiaggregant, Anticoagulant and Antioxidant Activities

Abstract: Natural monoterpenes and their derivatives are widely considered as effective ingredients for the design and production of new biologically active compounds with high antioxidant, antimicrobial and anti-protozoa properties. In this study, we synthesized two series of thiotherpenoids “sulfide-sulfoxide-sulfone”, with different bicyclic monoterpene skeleton (bornane and pinane) structures. The effect of the obtained compounds on platelet aggregation was investigated by using the molecular docking technique. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous reports have shown that monoterpenes exhibit anticoagulant activities by affecting the hemostasis process. They can reduce collagen-induced platelet aggregation, induce antithrombotic reactions and block the P2Y12 platelet receptor [46,47]. Citrus caused the inactivation of thrombin and a decrease in the concentration of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that monoterpenes exhibit anticoagulant activities by affecting the hemostasis process. They can reduce collagen-induced platelet aggregation, induce antithrombotic reactions and block the P2Y12 platelet receptor [46,47]. Citrus caused the inactivation of thrombin and a decrease in the concentration of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, two series of "sulfide-sulfoxide-sulfone" thioterpenoids, differing from each other in the structure of their terpenic skeletons, have been described [9]. The obtained compounds, 1-3, present bornane series compounds; meanwhile, compounds 4-6 present the pinane series (Figure 1).…”
Section: Introductionmentioning
confidence: 96%